Analisis Faktor Risiko Kehamilan Ektopik - Budi Santoso (Jurnal Ners, 2011)
Introduction: Ectopic pregnancy is a pregnancy with extrauterine implantation. This situation is gynecologic emergency that contributes to maternal mortality. Therefore, early recognition, based on identification of the causes of ectopic pregnancy risk factors, is needed.Methods: The design descriptive observational. The samples were pregnant women who had ectopic pregnancy at Maternity Room, Emergency Unit, Dr. Soetomo Hospital, Surabaya, from 1 July 2008 to 1 July 2010. Sampling technique was total sampling using medical records.Result: Patients with ectopic pregnancy were 99 individuals out of 2090 pregnant women who searched for treatment in Dr. Soetomo Hospital. However, only 29 patients were accompanied with traceable risk factors.Discussion:. Most ectopic pregnancies were in the age group of 26-30 years, comprising 32 patients (32.32%), then in age groups of 31–35 years as many as 25 patients (25.25%), 18 patients in age group 21–25 years (18.18%), 17 patients in age group 36–40 years (17.17%), 4 patients in age group 41 years and more (4.04%), and the least was in age group of 16–20 years with 3 patients (3.03%). A total of 12 patients with ectopic pregnancy (41.38%) had experience of abortion and 6 patients (20.69%) each in groups of patients with ectopic pregnancy who used family planning, in those who used family planning as well as ectopic pregnancy patients with history of surgery. There were 2 patients (6.90%) of the group of patients ectopic pregnancy who had history of surgery and history of abortion. The incidence rate of ectopic pregnancy was 4.73%, mostly in the second gravidity (34.34%), whereas the nulliparous have the highest prevalence of 39.39%. Acquired risk factors, i.e. history of operations was 10.34%, patients with family planning 20.69%, patients with history of abortion 41.38%, patients with history of abortion and operation 6.90% patients with family and history of abortion was 20.69%.